An ordinary man : the surprising life and historic presidency of Gerald R. Ford - Smith, Richard Norton, 1953- (Harper, 2023)
For many Americans, President Gerald Ford was the genial accident of history who controversially pardoned his Watergate-tarnished predecessor, presided over the fall of Saigon, and became a punching bag on Saturday Night Live. Yet as Richard Norton Smith reveals in a book full of surprises, Ford was an underrated leader whose tough decisions and personal decency look better with the passage of time. Drawing on hundreds of interviews and thousands of documents, Smith recreates Ford's hardscrabble childhood in Michigan, his early anti-establishment politics and lifelong love affair with the former Betty Bloomer, whose impact on American culture he predicted would outrank his own. As president, Ford guided the nation through its worst Constitutional crisis since the Civil War and broke the back of the most severe economic downturn since the Great Depression--accomplishing both with little fanfare or credit (at least until 2001 when the JFK Library gave him its prestigious Profile in Courage Award in belated recognition of the Nixon pardon). Less coda than curtain raiser, Ford's administration bridged the Republican pragmatism of Eisenhower and Nixon and the more doctrinaire conservatism of Ronald Reagan. His introduction of economic deregulation would transform the American economy, while his embrace of the Helsinki Accords hastened the collapse of the Soviet Union. Illustrated with sixteen pages of black-and-white photos, this definitive biography, a decade in the making, will change history's views of a man whose warning about presidential arrogance ("God help the country") is more relevant than ever.